Methodological Basis of Assessment of Innovative Potential in the Regional Management System - KRASNOSTANOVA, Nataliia E.; MAIDANIUK, Serhii I.; PRYVALOVA, Nataliia V.; AKYMENKO, Natalia V. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2019)
The article presents the features of administrative means of regulating the economy. Consider the main tasks of integration of the regional innovation space, the role of an organizational model for the formation of the interaction of regional subjects of innovation in the context of the formation of the innovation core of modernization processes. Also, the innovative potential of the Odessa region in terms of the integral indicator of innovation potential, weighting factors of the components of the integral indicator of the level of innovation potential, generalized indicators of the scientific potential, the level of potential of innovative developments and the susceptibility (susceptibility) of innovations are evaluated and analyzed.